2023
DOI: 10.1186/s12958-022-01053-7
|View full text |Cite
|
Sign up to set email alerts
|

Double-edged sword: effects of human sperm reactive oxygen species on embryo development in IVF cycles

Abstract: Background The exact role of sperm reactive oxygen species (ROS) in early embryo development has yet to be fully identified, and most of existing research did not differentiate female infertility factors, ignoring the importance of oocyte quality in embryo development and the large differences in oocyte quality in women with infertility of different etiologies. And there has been no relevant report on whether different types of sperm ROS have distinct effects on embryo development. This study a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Liu and colleagues reported that sperm mitochondrial ROS in cleavage-stage embryos have conflicting impacts depending on whether the female patient had normal ovulation. A high percentage of sperm producing a sufficient amount of ROS resulted in good development rates of day-3 embryos in anovulation patients, even though enhanced sperm mitochondrial ROS hindered embryo development in patients with normal ovulation [ 29 ]. This could be due to the fact that a small, physiological amount of ROS is necessary to trigger sperm capacitation, and acrosome reaction which are essential for embryo development [ 199 201 ].…”
Section: Effect Of Sperm Mitochondrial Dysfunction On Fertilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu and colleagues reported that sperm mitochondrial ROS in cleavage-stage embryos have conflicting impacts depending on whether the female patient had normal ovulation. A high percentage of sperm producing a sufficient amount of ROS resulted in good development rates of day-3 embryos in anovulation patients, even though enhanced sperm mitochondrial ROS hindered embryo development in patients with normal ovulation [ 29 ]. This could be due to the fact that a small, physiological amount of ROS is necessary to trigger sperm capacitation, and acrosome reaction which are essential for embryo development [ 199 201 ].…”
Section: Effect Of Sperm Mitochondrial Dysfunction On Fertilizationmentioning
confidence: 99%
“…Different procedures in ART labs have also been suggested to negatively affect sperm mitochondrial health in different ways [ 27 ]. Given the conflicting data regarding the impact of sperm mitochondrial dysfunction on pregnancy outcomes and ART success [ 28 , 29 ], this systematic review aims to critically evaluate existing literature. Our focus is on how a deeper understanding of mitochondrial dysfunction can inform the development of novel ART strategies to improve male infertility treatment.…”
Section: Introductionmentioning
confidence: 99%